Service Decisions Based on Social, Psychological, and Trust Factors Using Positive Emotional Stimulus - Mokhammad Ridha (Journal of Economy, Accounting and Management Science (JEAMS), 2023)
This study's goal was to identify the direct influence of social, psychological, and trust factors along with positive emotions on individuals' decisions to select physiotherapy services. At the Pain Relief Clinic Surabaya, subjects for physiotherapy were chosen. The decision to choose physiotherapy was a linked variable in this study; the independent variables were social, psychological, and trust aspects. Quantitative research employing survey techniques is the method used. Testing data tools, traditional acceptability tests, multiple linear regression tests, hypothesis testing, and deterministic analysis were all used in the data analysis. The results of the processed study show that psychological factors and trust have scientifically proved effects on decisions about physiotherapy services. Positive emotions have been shown to have a substantial impact on decisions for physiotherapy services based on social considerations and trust.